Fabrication of photo-cross-linked polyethyleneimine-based barriers for CO2 capture - KAHRAMAN, MEMET VEZİR (WILEY-BLACKWELL, 2015)
In this study, first, polyethyleneimine was acrylated and mixed with polyvinyl alcohol solution to prepare photo-crosslinked polyethyleneimine (PEI)-based nanofibers by utilizing ultraviolet and electrospinning technique at the same time. For CO2 permeability testing, same formulations were prepared by using solvent casting technique and exposed to ultraviolet light to have polyethyleneimine-based membrane films. The chemical structures of the nanofibers were characterized by Fourier transform infrared spectroscopy. The thermal properties of nanofibers were examined by thermal gravimetric analysis and differential scanning calorimeter. The morphology of nanofibers was investigated by scanning electron microscopy. CO2 permeabilities of samples were also measured. Copyright (C) 2015 John Wiley & Sons, Ltd.
Keywords: CO2 capture; membrane; nanofiber; electrospinning; photo-crosslinked; NANOFIBERS; MEMBRANES